2012
DOI: 10.1080/02640414.2012.718089
|View full text |Cite
|
Sign up to set email alerts
|

Trait self-esteem and claimed self-handicapping motives in sports situations

Abstract: We examined the relationship between physical self-esteem and claimed self-handicapping among athletes by taking motives into consideration. In Study 1, 99 athletes were asked to report their tendency to engage in claimed self-handicapping for self-protective and self-enhancement motives (trait measures). Low self-esteem athletes reported a higher tendency to engage in claimed self-handicapping for these two motives compared with high self-esteem athletes. Neither low nor high self-esteem athletes reported a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
0
7
0
4
Order By: Relevance
“…Moreover, Zuckerman and Tsai (2005) found that, over time, chronic self-handicappers were less well adjusted, reported an increase in substance abuse, and were less intrinsically motivated at work. Many studies have shown that lower self-esteem is related to increased self-handicapping (e.g., Finez, Berjot, Rosnet, Cleveland, & Tice, 2012; Rhodewalt, 1990; Spalding & Hardin, 1999; Zuckerman & Tsai, 2005). In Studies 3a and 3b, we tested the role that beliefs about deserving bad outcomes play in this link between self-esteem and self-handicapping.…”
Section: Studies 3a and 3b: Effects Of Good/bad Breaks On Self-handicmentioning
confidence: 99%
“…Moreover, Zuckerman and Tsai (2005) found that, over time, chronic self-handicappers were less well adjusted, reported an increase in substance abuse, and were less intrinsically motivated at work. Many studies have shown that lower self-esteem is related to increased self-handicapping (e.g., Finez, Berjot, Rosnet, Cleveland, & Tice, 2012; Rhodewalt, 1990; Spalding & Hardin, 1999; Zuckerman & Tsai, 2005). In Studies 3a and 3b, we tested the role that beliefs about deserving bad outcomes play in this link between self-esteem and self-handicapping.…”
Section: Studies 3a and 3b: Effects Of Good/bad Breaks On Self-handicmentioning
confidence: 99%
“…Düşük benlik saygısına sahip olan bireylerin başarıyla ilgili beklentilerinin düşük; başarısızlık durumunda başka insanların onlar için olumsuz düşüncelere sahip olduğu ve başarısızlığa dair kaygılarının olmasının benlik saygısı düşük bireyleri, benliğini koruma ya da geliştirmeye yöne-lik stratejilere başvurmaya yönlendirmesi bu çalışmanın bulgularını destekler niteliktedir. 24,49 Benlik saygısı düşük olan birey, performans sonrası olası bir başarısızlık yaşaması hâlinde utanç duygusunu yaşayabilmekte ve diğer insanlara karşı kendini değersiz hissedebilmektedir. Self'e göre, benliğinin tehdit edici durumla karşı karşıya kalması kendini sabotaj stratejilerini kullanılması için yeterli bir sebep olabilmektedir.…”
Section: Discussionunclassified
“…20,21,24,25,50 Prapavessis ve Grove tarafından yapılan bir çalışmada, 109 erkek golf oyuncusunun benlik saygıları ile kendini sabotaj eğilimleri incelenmiş ve düşük benlik saygısına sahip olan sporcuların kendini sabotaj eğiliminde oldukları belirlenmiştir. 25 Bir başka çalışmada, 31 basketbol oyuncusunun ego tehditi altında kaldıkları durumlarda, düşük benlik saygısına sahip olan sporcuların kendini sabotaj stratejilerine başvur-dukları sonucuna varılmıştır.…”
Section: Discussionunclassified
See 2 more Smart Citations